Analisis Faktor-Faktor Yang Mempengaruhi Penerapan Anggaran Berbasis Kinerja (Studi Pada Organisasi Perangkat Daerah Kabupaten Boyolali) - Diastuti, Pradibta, Drs. Muhammad Abdul Aris, M.Si (2017)
This research aimed to analyze the influence of human resources, leadership style, organizational commitment, reward and punishment the applicacation of the performance-based budgeting. The population in this study is the civil servants who work in the district Boyolali regional organizations in the finance and accounting. Sample in this study consisted of a number of selected member of the population. Sampling was done with the purposive sampling with the sample amount to 150 employees. Hypothesis test results showed that the human resources, organizational commitment, reward and punishment influence on the implementation of performance-based budgeting. While, leadership style not influence on the implementation implementation of performance-based budgeting.